2018
DOI: 10.1038/s41467-018-03329-2
|View full text |Cite
|
Sign up to set email alerts
|

Ice-volume-forced erosion of the Chinese Loess Plateau global Quaternary stratotype site

Abstract: The International Commission on Stratigraphy (ICS) utilises benchmark chronostratigraphies to divide geologic time. The reliability of these records is fundamental to understand past global change. Here we use the most detailed luminescence dating age model yet published to show that the ICS chronology for the Quaternary terrestrial type section at Jingbian, desert marginal Chinese Loess Plateau, is inaccurate. There are large hiatuses and depositional changes expressed across a dynamic gully landform at the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
87
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(105 citation statements)
references
References 81 publications
6
87
0
Order By: Relevance
“…Whether climatically or locally driven, a number of gaps in loess records have been reported at multiple locations (e.g. Dong et al ., 2015; Stevens et al ., 2018), highlighting the danger of the loess continuity assumption. The profiles at Erdut provide a unique view of the issue as profile 4 shows a hiatus that would not be recognised due to the lack of lithological changes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Whether climatically or locally driven, a number of gaps in loess records have been reported at multiple locations (e.g. Dong et al ., 2015; Stevens et al ., 2018), highlighting the danger of the loess continuity assumption. The profiles at Erdut provide a unique view of the issue as profile 4 shows a hiatus that would not be recognised due to the lack of lithological changes.…”
Section: Resultsmentioning
confidence: 99%
“…They often span multiple glacial–interglacial cycles and offer long‐term Quaternary records in regions where other long‐term archives are frequently absent. Therefore they provide a unique insight into the Earth's past and an opportunity to compare and correlate terrestrial signals with ice‐ and marine‐ core records (Kukla, 1977; Antoine et al ., 2009; Stevens et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was later found that the pIRIR290 signal intensity was still sufficiently high to guarantee precise measurements even when the prior-IR stimulation temperature was as high as 260 °C, and thus Buylaert et al [88] applied the pIRIR200, 290 protocol to date the last interglacial paleosol (S1) in the Chinese Loess Plateau. Stevens et al [89] reported that De values were underestimated when the prior-IR stimulation temperature was below 140 °C, but a De plateau had…”
Section: Comparison Between Different Pirir Protocolsmentioning
confidence: 99%
“…The uplift of the Tibetan Plateau during late Cenozoic, the aridification of the Asian interior, and global climatic cooling are thought to have been major causal factors of regional erosion and the deposition and the evolution of the red clay‐loess sequence on the Chinese Loess Plateau (CLP) (An et al, ; Liu, ; Maher, ; Stevens et al, ; Zan, Fang, et al, ). Consequently, these red clay‐loess sequences are regarded as one of the most valuable terrestrial archives for deciphering the history of the aridification of the Asian interior and tectonic‐climate interactions during the late Cenozoic (An et al, ; Burbank & Li, ; Maher, ).…”
Section: Introductionmentioning
confidence: 99%